(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
As a result of quantitative data analysis by laboratory and field experiments quantitative patterns of water migration in compacted silty loam embankment, including the stabilized (or final) clay soil moisture values, depending on their type (number plasticity), soil skeleton density, embankment height and time «rest» of the subgrade before it’s operation are established. The soil moisture changes graphs at what the loam was compacted from soil skeleton density and stabilized soil moisture of already compacted loam after the subgrade «rest» from soil skeleton density are plotting in the article. The empirical dependence of compacted silty loams stabilized moisture for their multilayer consolidation is obtained. Empirical dependence parameter corresponds to maximum molecular moisture capacity at what it is advisable to do the subgrade clay soils multilayer consolidation for the ensuring their long-term strength. Keywords: water migration, compacted loam, soil skeleton density, plasticity number, stabilized moisture, two-factor analysis, empirical dependence.